Sustainable Development of a Region. Case Study - Kazakhstan - BESPALYY, Sergey Vladimirovich (Journal of Environmental Management and Tourism; Vol 12 No 2 (2021): JEMT Volume XII Issue 2(50) Spring 2021, 2021)
The article provides an overview of the region's development, while suggesting how to assess sustainable development from the point of view of the ecological component, as well as social and economic. The paper presents a combination of assessments that used data and indicators (if any), as well as expert opinions for a comprehensive assessment. Although there are some key points and controversial issues, the development of Bayanaul l district can be assessed as sustainable. In general, there is a positive, general economic situation and the level of income of most people, good environmental conditions and rich biodiversity, stable social structure, and the identity of people in the area. On the contrary, there are various threats such as engineering and transport infrastructure, an increased flow of people from tourism, degradation of habitats, declining species richness and intensification of agriculture.